FORUM GROUP DISCUSSIONS (FGD) PENGEMBANGAN PERANGKAT PEMBELAJARAN KURIKULUM TERBARU - Hajerah, Hajerah; Syamsuardi; Kurnia R, Rika; Herlina; Herman; Nur Maharani Islami, Andi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The development of the education curriculum requires educators to continuously adapt and develop learning tools that align with current needs. This community service activity aims to assist educators in understanding and designing learning tools in accordance with the latest curriculum through a Forum Group Discussion (FGD). The methods used in this activity include interactive discussions, presentations on the latest curriculum concepts, and hands-on practice in developing learning tools. The results of this activity indicate that FGD can enhance participants' understanding of curriculum concepts and implementation while encouraging collaboration in creating more effective learning tools. Thus, this activity makes a tangible contribution to improving the quality of education. Keywords: Curriculum, learning tools, strategies.